A global ocean climatology of preindustrial and modern ocean δ13C. Issue 3 (6th March 2017) - Eide, Marie; Olsen, Are; Ninnemann, Ulysses S.; Johannessen, Truls
Abstract: We present a global ocean climatology of dissolved inorganic carbon δ 13 C (‰) corrected for the 13 C‐Suess effect, preindustrial δ 13 C. This was constructed by first using Olsen and Ninnemann's (2010) back‐calculation method on data from 25 World Ocean Circulation Experiment cruises to reconstruct the preindustrial δ 13 C on sections spanning all major oceans. Next, we developed five multilinear regression equations, one for each major ocean basin, which were applied on the World Ocean Atlas data to construct the climatology. This reveals the natural δ 13 C distribution in the global ocean. Compared to the modern distribution, the preindustrial δ 13 C spans a larger range of values. The maxima, of up to 1.8‰, occurs in the subtropical gyres of all basins, in the upper and intermediate waters of the North Atlantic, as well as in mode waters with a Southern Ocean origin. Particularly strong gradients occur at intermediate depths, revealing a strong potential for using δ 13 C as a tracer for changes in water mass geometry at these levels. Further, we identify a much tighter relationship between δ 13 C and apparent oxygen utilization (AOU) than between δ 13 C and phosphate. This arises because, in contrast to phosphate, AOU and δ 13 C are both partly reset when waters are ventilated in the Southern Ocean and underscore that δ 13 C is a highly robust proxy for past changes in ocean oxygen content and ocean ventilation. Our global preindustrial δ 13 C climatology is openly accessible and can be used, for example, for improved model evaluation and interpretation of sediment δ 13 C records. Key Points: A global ocean climatology of the preindustrial C‐13 distribution, corrected for anthropogenic influences Preindustrial C‐13 spans a larger range of values compared to the modern distribution, with particularly strong intermediate ocean gradients C‐13 is found to be a highly robust proxy for past changes in oxygen content and ocean ventilation